A three-centre experience with adalimumab for the treatment of non-infectious uveitis - Dobner, Bianca C.; Max, Regina; Becker, Matthias D.; Mackensen, Friederike (British journal of ophthalmology, 2013)
Objective The aim of this study was to assess the efﬁcacy of adalimumab in patients with active noninfectious uveitis in three different centres.Methods In a retrospective study we identiﬁed patients from our databases who were treated with adalimumab. The composite outcome measure for efﬁcacy included reduction of macular oedema by optic coherence tomography, visual acuity, anterior chamber cells, reduction of frequency of ﬂares and reduction of prednisone dose during the treatment. At least one of the criteria had to be improved and none worsened to declare treatment as effective.Results 60 patients with an average age of 37.3 years (range 4-71 years) were treated with adalimumab over an average follow-up period of 87.9 weeks (range 12-222 weeks). The indication for treatment was in 41 (68.3%) patients the activity of both uveitis and systemic disease and in 19 (31.7%) patients uveitis activity only. 15 (25%) patients were treated before with etanercept and 10 (16.7%) patients with inﬂiximab. 49 out of 60 (81.7%) patients improved, while the other 11 (18.3%) patients did not meet improvement criteria and were given additional or alternative immunosuppressive treatment. At the last follow-up, 47 (78.3%) patients were still on adalimumab treatment. 13 (21.6%) patients stopped adalimumab treatment, due to inefﬁcacy in eight, another three patients due to side effects (liver enzyme elevation and furunculosis), one patient due to pregnancy and one patient died.Conclusions This large retrospective case series showed that adalimumab is effective in up to 80% of patients with uveitis.